Exogenous Melatonin Application Delays Senescence and Improves Postharvest Antioxidant Capacity in Blueberries - Jie Li; Ying Wang; Jinying Li; Yanan Li; Chunze Lu; Zihuan Hou; Haiguang Liu; Lin Wu (Agronomy)
Blueberries are highly prone to postharvest decay, resulting in significant nutrient loss and economic damage. Current research on the postharvest storage of blueberries primarily focuses on storage techniques, while the underlying mechanisms remain insufficiently explored. To further explore the role of exogenous melatonin (MT) in delaying the senescence of blueberry fruit, this study treated fruits with sterile water (control) and 300 μmol·L−1 MT during the pink fruit stage. After maturation, the fruits were stored at 4 °C for 30 days, and we investigated the effects of exogenous MT on postharvest blueberry quality, reactive oxygen species (ROS) metabolism, antioxidant enzyme activities, and the expression of related genes. The results showed that, compared to the control, 300 μmol·L−1 MT effectively delayed the increase in fruit decay rate and the decline in firmness, while enhancing the total soluble solids (TSS) content and ascorbic acid (AsA) levels. It also reduced the accumulation of malondialdehyde (MDA), hydrogen peroxide (H2O2), and the production rate of superoxide anion (O2−), while maintaining higher activities of ascorbate peroxidase (APX), superoxide dismutase (SOD), and catalase (CAT). Furthermore, MT treatment upregulated the expression of antioxidant enzyme-related genes VcSOD1, VcSOD2, and VcAPX3. These findings indicate that treating blueberries with 300 μmol·L−1 MT at the pink fruit stage improves postharvest quality, alleviates oxidative damage, and delays senescence. This study provides a theoretical foundation and practical reference for blueberry storage and preservation, laying the groundwork for further understanding the regulatory mechanisms of exogenous MT in postharvest fruit senescence.